2015
DOI: 10.1177/1532673x15576952
|View full text |Cite
|
Sign up to set email alerts
|

Earmarks and Subcommittee Government in the U.S. Congress

Abstract: In recent years, considerable scholarly attention has focused on earmarks, the quintessential example of pork barrel politics. We assess the degree to which existing theories can explain the distribution of earmarks in the U.S. House of Representatives. First, drawing on informal interviews with individuals on Capitol Hill regarding the earmark process, we argue that assessing institutional and constituency-level factors that affect the earmark receipts of individual members requires examination at the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…Balla et al () find that members of the Senate (but not House) Appropriations Committee deliver more academic earmarks than do non‐members. A spate of recent articles using the same data from Figure on earmark sponsorship in the 110th and 111th congresses find that members of the House and Senate Appropriations Committees receive more earmarks than non‐members (Clemens, Crespin, and Finocchiaro ; Lazarus , ; Lazarus and Steigerwalt ). Earmarking advantages have also been found for some but not all Senate Appropriations subcommittees (Crespin and Finocchiaro ) and for some authorizing committees in the House (Lazarus ).…”
Section: Related Literaturementioning
confidence: 99%
“…Balla et al () find that members of the Senate (but not House) Appropriations Committee deliver more academic earmarks than do non‐members. A spate of recent articles using the same data from Figure on earmark sponsorship in the 110th and 111th congresses find that members of the House and Senate Appropriations Committees receive more earmarks than non‐members (Clemens, Crespin, and Finocchiaro ; Lazarus , ; Lazarus and Steigerwalt ). Earmarking advantages have also been found for some but not all Senate Appropriations subcommittees (Crespin and Finocchiaro ) and for some authorizing committees in the House (Lazarus ).…”
Section: Related Literaturementioning
confidence: 99%
“…These areas are important centers of activity for the US military and defense contractors. Clemens, Crespin, and Finocchiaro () find that district demand plays a pronounced role in influencing earmark allocation for the Defense, Military Construction, and Agriculture subcommittees whereas demand is not significant for many of the other appropriations bills. Finally, the Appropriations Power Index variable is significant over the entire set of observations.…”
Section: Resultsmentioning
confidence: 99%
“…These models draw upon two dominant theories of congressional behavior: distributive theories that explain pork as a result of electorally motivated legislators (Ferejohn ; Mayhew ; Shepsle and Weingast ) and partisan theories that posit majority leaders who use pork, amongst other tools, to achieve party goals (Cox and McCubbins ). In this vein, scholars have found that leaders sometimes use earmarks to protect vulnerable incumbents (Engstrom and Vanberg ; Lazarus ) and have investigated whether demand for particular projects from the district is an important determinant of earmark awards (Clemens, Crespin, and Finocchiaro , ; Lazarus ). Moreover, it is now commonly accepted that legislators' standing in Congress—especially status as a member of the Appropriations Committee—is an important component of pork awards (Engstrom and Vanberg ; Lee ).…”
Section: Distributing Pork In Legislaturesmentioning
confidence: 99%
“…Yet, committees still appear to be influential forces. Congressional committees still have influence over policymaking (Adler and Wilkerson ; Woon and Anderson ), policy implementation (Ainsworth, Harward, and Moffett ; Shipan ), and the allocation of federal funds (Clemens, Crespin, and Finocchiaro ). Committees continue to be the target of lobbying efforts (Esterling ), and members continue to work hard to obtain ideal committee assignments (Frisch and Kelly ), find their assignments to be valuable (Grimmer and Powell ), and find their legislative lives structured by committee activity (Lipinski ).…”
Section: Traditional Processes and Committee Powermentioning
confidence: 99%
“…Indeed, the very fact that the job of providing cues is delegated to committee leaders reflects their reputations as knowledgeable on the issues. As Curry () finds, rank‐and‐file lawmakers are far more trusting of information provided by committee leaders than party leaders.…”
mentioning
confidence: 99%